Benchmarking Hyperparameter Variations on Transfer Learning Models for Coral Reefs Classification: A Case Study on Efficientnetv2 and Mobilenetv2 - Bimantyoso Hamdikatama; Dedi Gunawan; Kusrini Kusrini (Jurnal Nasional Komputasi dan Teknologi Informasi (JNKTI), 2025)
Abstract - Coral reef recognition using transfer learning models is a critical area of research to enhance automated monitoring and conservation efforts. This study examines the impact of hyperparameter tuning on the performance of two models, EfficientNetV2 and MobileNetV2, in recognizing coral reef conditions such as bleaching, physical damage, and algae overgrowth. Bayesian Optimization is evaluated as an automated hyperparameter tuning method alongside Grid Search, Random Search, and Manual Trial-based approaches. The results reveal that Bayesian Optimization achieves competitive accuracy (up to 0.81) and balances computational efficiency with performance, requiring fewer trials compared to manual optimization. Notably, Bayesian Optimization reduces training time while maintaining high metrics such as Precision and Specificity. These findings highlight the effectiveness of Bayesian Optimization in improving model performance for coral reef recognition, offering a reliable and efficient solution to support conservation decision-making. This approach also demonstrates potential for broader applications in classification and regression tasks.Keywords: EfficientNetV2, MobileNetV2, Optimization, Coral Reefs Abstrak - Pengenalan terumbu karang menggunakan model pembelajaran transfer adalah bidang penelitian yang penting untuk meningkatkan upaya pemantauan dan konservasi otomatis. Penelitian ini menguji dampak penyetelan hyperparameter pada kinerja dua model, EfficientNetV2 dan MobileNetV2, dalam mengenali kondisi terumbu karang seperti pemutihan, kerusakan fisik, dan pertumbuhan berlebih alga. Bayesian Optimization dievaluasi sebagai metode penyetelan hiperparameter otomatis bersama dengan Pencarian Grid, Pencarian Acak, dan pendekatan berbasis Uji Coba Manual. Hasilnya menunjukkan bahwa Bayesian Optimization mencapai akurasi yang kompetitif (hingga 0,81) dan menyeimbangkan efisiensi komputasi dengan kinerja, sehingga membutuhkan lebih sedikit uji coba dibandingkan dengan pengoptimalan manual. Selain itu, Bayesian Optimization mengurangi waktu pelatihan dengan tetap mempertahankan metrik yang tinggi seperti Presisi dan Spesifisitas. Temuan ini menyoroti efektivitas Optimasi Bayesian dalam meningkatkan kinerja model untuk pengenalan terumbu karang, menawarkan solusi yang andal dan efisien untuk mendukung pengambilan keputusan konservasi. Pendekatan ini juga menunjukkan potensi untuk aplikasi yang lebih luas dalam tugas klasifikasi dan regresi.Kata kunci: EfisienNetV2, MobileNetV2, Optimasi, Terumbu Karang